2016
DOI: 10.1371/journal.pone.0168690
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Avipoxvirus in House Sparrows in Spain

Abstract: Avipoxvirus (APV) is a fairly common virus affecting birds that causes morbidity and mortality in wild and captive birds. We studied the prevalence of pox-like lesions and genetic diversity of APV in house sparrows (Passer domesticus) in natural, agricultural and urban areas in southern Spain in 2013 and 2014 and in central Spain for 8 months (2012–2013). Overall, 3.2% of 2,341 house sparrows visually examined in southern Spain had cutaneous lesions consistent with avian pox. A similar prevalence (3%) was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Several surveys have been carried out in house sparrows (Passer domesticus), permitting the comparison of prevalences of APV in the same species in different ecosystems and regions. Van Riper et al [30] found prevalences of 2.5% and 4.9% of active and inactive avian pox lesions in 81 house sparrows captured in Hawaii (albeit a limited sample size) and similar prevalences of 3.1% were reported in an extensive sample size (2729) in Spain [46]. In contrast, Smits et al [48] did not report any clinical signs of infection in Spanish sparrows (P. hispanolensis) in the Canary Islands (n = 128).…”
Section: Prevalence Of Pox Lesions and Apv Infections In Wild Birdsmentioning
confidence: 70%
See 2 more Smart Citations
“…Several surveys have been carried out in house sparrows (Passer domesticus), permitting the comparison of prevalences of APV in the same species in different ecosystems and regions. Van Riper et al [30] found prevalences of 2.5% and 4.9% of active and inactive avian pox lesions in 81 house sparrows captured in Hawaii (albeit a limited sample size) and similar prevalences of 3.1% were reported in an extensive sample size (2729) in Spain [46]. In contrast, Smits et al [48] did not report any clinical signs of infection in Spanish sparrows (P. hispanolensis) in the Canary Islands (n = 128).…”
Section: Prevalence Of Pox Lesions and Apv Infections In Wild Birdsmentioning
confidence: 70%
“…Age and immune function are reported to be important factors explaining withinspecies differences in APV prevalence. In nearly all studies, avipox lesions are significantly more frequent in juveniles than in adults [40,[44][45][46][47]-this is anticipated, as first-year birds will not have acquired specific immunity to APV infection. Le Loc'h et al [41] showed that this pattern was true only for houbara bustards in Morocco but not in the United Arab Emirates, where pox infection affected juveniles and adults alike.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Its ability to hybridize with other species makes it adaptable to new environments 9 , making this mosquito a challenging vector to control. In addition, Culex quinquefasciatus is the primary vector for avian malaria and avian pox, posing existential threats to island avifauna 10 12 . As an example, the invasive Culex quinquefasciatus in Hawai’i has contributed to the extinction of several Honeycreeper species and continues to threaten other susceptible species on the islands 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional PCR has been used to detect avian pox in the past [2,4] as well as to determine prevalence and genetic diversity of avian pox [27,28]; however, there are still limitations. In analyses using solely conventional PCR, parasite or viral load is difficult to determine [29] and as it relies on downstream visualization, products are handled more than once thus increasing the risk of viral contamination [30].…”
Section: Discussionmentioning
confidence: 99%